De la Federación de oficio a la Unión de ramos anexos: los constructores de calzado y los obreros en pieles ante el reto de la solidaridad a escala nacional (1870-1890) - Joël Delhom (Cahiers de Civilisation Espagnole Contemporaine)
In order to make more effective workers’ solidarity and throw together the foundations of the collectivist society of the future, the internationalist trade-unions (fre and ftre) organized in the last third of the xixth century trade federations and unions of complementary trades on a national scale. The case of the shoemaking and leather industries brings to light their statutes’ gradual evolutions, their goals and dynamics. Seven congresses are analysed.